The performance and exhaust emissions of a diesel engine fuelled with Calophyllum inophyllum- palm biodiesel - Damanik N.; Ong H.C.; Mofijur M.; Tong C.W.; Silitonga A.S.; Shamsuddin A.H.; Sebayang A.H.; Mahlia T.M.I.; Wang C.-T.; Jang J.-H. (MDPI AG, 2023)
Nowadays, increased interest among the scientific community to explore the Calophyllum inophyllum as alternative fuels for diesel engines is observed. This research is about using mixed Calophyllum inophyllum-palm oil biodiesel production and evaluation that biodiesel in a diesel engine. The Calophyllum inophyllum-palm oil methyl ester (CPME) is processed using the following procedure: (1) the crude Calophyllum inophyllum and palm oils are mixed at the same ratio of 50:50 volume %, (2) degumming, (3) acid-catalysed esterification, (4) purification, and (5) alkalinecatalysed transesterification. The results are indeed encouraging which satisfy the international standards, CPME shows the high heating value (37.9 MJ/kg) but lower kinematic viscosity (4.50 mm2/s) due to change the fatty acid methyl ester (FAME) composition compared to Calophyllum inophyllum methyl ester (CIME). The average results show that the blended fuels have higher Brake Specific Fuel Consumption (BSFC) and NOx emissions, lower Brake Thermal Efficiency (BTE), along with CO and HC emissions than diesel fuel over the entire range of speeds. Among the blends, CPME5 offered better performance compared to other fuels. It can be recommended that the CPME blend has great potential as an alternative fuel because of its excellent characteristics, better performance, and less harmful emission than CIME blends. 2019 by the authors.